2004
DOI: 10.1063/1.1734689
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of wide stacking faults in nanocrystalline Al

Abstract: A full dislocation often dissociates into two partial dislocations enclosing a stacking fault ͑SF͒ ribbon. The SF width significantly affects the mechanical behavior of metals. Al has very high stacking fault energy and, consequently, very narrow SF width in its coarse-grained state. We have found that some SFs in nanocrystalline Al are surprisingly 1.4 -6.8 nm wide, which is 1.5-11 times higher than the reported experimental value in single crystal Al. Our analytical model shows that such wide SFs are formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(94 citation statements)
references
References 20 publications
10
80
1
3
Order By: Relevance
“…Conversely, slip occurs in CG or NG materials when a lead partial dislocation is followed by a trailing partial dislocation on the same {111} plane 15 . A difference between CG metals and NG metals is that in NG metals the boundaries supply the partial dislocations needed for slip or twinning 1,2,4,18,19 . Molecular dynamics has shown that grain boundaries and even pristine phase boundaries can nucleate partial dislocations into Cu 33,34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, slip occurs in CG or NG materials when a lead partial dislocation is followed by a trailing partial dislocation on the same {111} plane 15 . A difference between CG metals and NG metals is that in NG metals the boundaries supply the partial dislocations needed for slip or twinning 1,2,4,18,19 . Molecular dynamics has shown that grain boundaries and even pristine phase boundaries can nucleate partial dislocations into Cu 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…This nucleation mechanism permits several intersecting twins to form, potentially adversely affecting fracture behaviour 16,17 . Conversely, in NG metals, twins nucleate predominantly from reactions within grain boundaries 1,2,4,18,19 . With twins formed in this way, several desirable properties emerge, such as high strength, hardness, ductility and thermal stability, not seen in the CG counterparts 11 .…”
mentioning
confidence: 99%
“…where E b is the energy per unit length of a dislocation with a Burgers vector is at an angle b to the dislocation line, G is the shear modulus, m is the Poisson's ratio, R can be estimated as the grain size d, and r 0 can be estimated as the Burgers vector b [44]. Eq.…”
Section: Cross-slip Of the 30°partial At The Twin Boundarymentioning
confidence: 99%
“…The formation of L-C locks also needs the participation of stacking faults. NC materials are known to produce wider stacking faults than their coarsegrained counterparts, especially near the grain boundaries [24,25], and therefore should be more favorable to producing L-C locks. Since the cross-slip of perfect dislocations occurs more readily near grain boundaries, where stress concentrations exist [23], there should be higher density of L-C locks, and consequently higher dislocation accumulation near grain boundaries.…”
mentioning
confidence: 99%